28 High yielding irrigated lowland breeding lines exceeding Sahel 108 and ISRIZ-07 by up to 36% identified in replicated yield trials in Senegal - CGIAR Research Program on Rice (2020)
In 2 replicated yield trials conducted at Ndiaye, Senegal during the dry and wet seasons of 2020 using 24 and 19 entries, respectively, 28 high yielding irrigated lowland breeding lines exceeding Sahel 108 and ISRIZ-09 by up to 36% were identified.